Synthesis, Characterisation and Pharmacological Screening of Macro Cyclic Vanadium (IV) Complexes - Vijay Kumar (Journal of Global Pharma Technology, 2018)
The coordination chemistry has wide applications in different fields. The arrangement of stable buildings with great natural applications is additionally testing these days. The strength of the buildings depends just on Ligands. The cyclic ring has greater steadiness when contrasted with other polydentate ligands. Vanadium can consolidate with macrocyclicligands. The nearness think about includes amalgamation and portrayal of three diverse full scale cyclic ligands by utilizing ethylene diamine and perchloric corrosive. Planning of vanadium edifices do by blending of VOSO4.H2O and integrated ligands. These buildings were described utilizing UV – Visible spectroscopy, FT-IR. Included with these electrochemical investigations of the building and cyclic voltammetry a technique. Anti microbial examination has been completed.